Recent Insight on the Management of Lupus Erythematosus Alopecia - Desai K; Miteva M (Dove Medical Press, 2021)
Karishma Desai, Mariya Miteva Dr. Phillip Frost Department of Dermatology and Cutaneous Surgery, University of Miami Miller School of Medicine, Miami, FL, USACorrespondence: Karishma DesaiDr. Phillip Frost Department of Dermatology and Cutaneous Surgery, University of Miami Miller School of Medicine, 1600 N.W. 10th Ave., RMSB Building Room 2023C, Miami, FL, 33136, USATel +1 305 243-5523Fax +1 305 243-5810Email kdesai66@med.miami.eduAbstract: Lupus erythematosus (LE) is a chronic autoimmune condition with a wide spectrum of clinical presentations. Alopecias, both non-scarring and scarring, frequently occur in the context of LE and can assume several different patterns. Furthermore, alopecia occurring with LE may be considered LE-specific if LE-specific features are present on histology; otherwise, alopecia is considered non-LE-specific. Non-scarring alopecia is highly specific to systemic LE (SLE), and therefore has been regarded as a criterion for the diagnosis of SLE. Variants of cutaneous LE (CLE), including acute, subacute, and chronic forms, are also capable of causing hair loss, and chronic CLE is an important cause of primary cicatricial alopecia. Other types of hair loss not specific to LE, including telogen effluvium, alopecia areata, and anagen effluvium, may also occur in a patient with lupus. Lupus alopecia may be difficult to treat, particularly in cases that have progressed to scarring. The article summarizes the types of lupus alopecia and recent insight regarding their management. Data regarding the management of lupus alopecia are sparse and limited to case reports, and therefore, many studies including in this review report the efficacy of treatments on CLE as a broader entity. In general, for patients with non-scarring alopecia in SLE, management is aimed at controlling SLE activity with subsequent hair regrowth. Topical medications can be used to expedite recovery. Prompt treatment is crucial in the case of chronic CLE due to potential for scarring and irreversible damage. First-line therapies for CLE include topical corticosteroids and oral antimalarials, with or without oral corticosteroids as bridging therapy. Second and third-line systemic treatments for CLE include methotrexate, retinoids, dapsone, mycophenolate mofetil, and mycophenolate acid. Additional topical and systemic medications as well as physical modalities used for the treatment of lupus alopecia and CLE are discussed herein.Keywords: discoid, hair loss, cicatricial, scarring, non-scarring